Barriers and Facilitators to Initiating and Completing Time-Limited Trials in Critical Care*. Issue 12 (December 2015) - Bruce, Courtenay R.; Liang, Cecilia; Blumenthal-Barby, Jennifer S.; Zimmerman, Janice; Downey, Andrea; Pham, Linda; Theriot, Lisette; Delgado, Estevan D.; White, Douglas
Abstract : Objectives: A time-limited trial is an agreement between clinicians and patients or surrogate decision makers to use medical therapies over a defined period of time to see if the patient improves or deteriorates according to agreed-upon clinical milestones. Although time-limited trials are broadly advocated, there is little empirical evidence of the benefits and risks of time-limited trials, when they are initiated, when and why they succeed or fail, and what facilitates completion of them. Our study objectives were to 1) identify the purposes for which clinicians use time-limited trials and 2) identify barriers and facilitators to initiating and completing time-limited trials. Design: Semistructured interviews: We analyzed interviews using qualitative description with constant comparative techniques. Setting: Nine hundred-bed, academic, tertiary hospital in Houston, Texas. Interviewees were from open medical, surgical, neurosurgical, and cardiovascular ICUs. Subjects: Thirty healthcare professionals were interviewed (nine surgeons, 16 intensivists, three nurse practitioners, and two "other" clinicians). Interventions: None. Measurements and Main Results: Interviewees reported initiating time-limited trials for three different purposes: to prepare surrogates and clinicians for discussion and possible shifts toward comfort-care only therapies, build consensus, and refine prognostic information. The main barriers to initiating time-limited trials involve clinicians' or surrogate decision makers' disagreement on setting a time limit. Barriers to completing time-limited trials include 1) requesting more time; 2) communication breakdowns because of rotating call schedules; and 3) changes in clinical course. Finally, facilitators to completing time-limited trials include 1) having defined goals about what could be achieved during an ICU stay, either framed in narrow, numeric terms or broad goals focusing on achievable activities of daily living; 2) applying time-limited trials in certain types of cases; and 3) taking ownership to ensure completion of the trial. Conclusions: An understanding of barriers and facilitators to initiating and completing time-limited trials is an essential first step toward appropriate utilization of time-limited trials in the ICUs, as well as developing educational or communication interventions with clinicians to facilitate time-limited trial use. We provide practical suggestions on patient populations in whom time-limited trials may be successful, the setting, and clinicians likely to benefit from educational interventions, allowing clinicians to have a fuller sense of when and how to use time-limited trials. Abstract : Supplemental Digital Content is available in the text.